2010
DOI: 10.1159/000322202
|View full text |Cite
|
Sign up to set email alerts
|

EEG Abnormalities Are Associated with Different Cognitive Profiles in Alzheimer’s Disease

Abstract: Objective: Our purpose was to investigate associations between different cognitive profiles and their underlying functional brain changes as measured by electroencephalogram (EEG) in Alzheimer’s disease (AD). Methods: EEG was obtained and neuropsychological performance assessed in 254 patients with AD. The EEGs were visually assessed for the presence of focal and/or diffuse abnormalities. Multivariate analysis of variance for repeated measures was performed with presence of focal and/or diffuse abnormalities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
3
13
0
Order By: Relevance
“…Occurrence of normal EEGs in some AD patients is in accordance with previous studies [8,35,40,41]. Smits et al [40] reported recently that visually assessed EEG abnormalities are associated with different cognitive profiles in AD. In their study 28% of AD patients had normal EEGs and a cognitive profile in which memory was mostly impaired.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Occurrence of normal EEGs in some AD patients is in accordance with previous studies [8,35,40,41]. Smits et al [40] reported recently that visually assessed EEG abnormalities are associated with different cognitive profiles in AD. In their study 28% of AD patients had normal EEGs and a cognitive profile in which memory was mostly impaired.…”
Section: Discussionsupporting
confidence: 89%
“…It is known that the main risk factors for AD and MCI have also been reported as risk factors for cardiovascular disease and could modify the clinical expression of parallel neurodegenerative processes in the brain [38,39]. Occurrence of normal EEGs in some AD patients is in accordance with previous studies [8,35,40,41]. Smits et al [40] reported recently that visually assessed EEG abnormalities are associated with different cognitive profiles in AD.…”
Section: Discussionsupporting
confidence: 77%
“…By employing this algorithm, 67 of the 69 CHNC patients were categorized as members of subgroup 1 (interval I), and 110 of the 113 CHCI patients were categorized as subgroup 2 (interval II). The classification used the 8 EEG channels (1,8,9,10,11,12,13, and 16) exhibiting the largest differences in relative beta power. We noted that beta power of patients on the highest channels (1, 10, and 12) displaying the 3-dimensional graph showed the difference directly.…”
Section: Discussionmentioning
confidence: 99%
“…Only 4 channels, 2(F3-C3), 4(P3-O1), 7(C4-P4), and 14(F8-T4), did not differ between CHCI and NC in relative beta power. Eight channels (1,8,9,10,11,12,13, and 16) exhibited the largest differences in relative beta power. Beta bandwidth signals of the above 8 EEG channels were selected for patients with post cerebral hemorrhage.…”
Section: The Eeg Analysis Techniquesmentioning
confidence: 96%
See 1 more Smart Citation